Legal Analysis Of The Application Of Article 363 Paragraph (1) 5 Of The Kuhp Towards The Criminal Act Of Aggravated Theft From The Perspective Of Islamic Law (Study of Decision Number 666/Pid.B/2025/PN Dps) - Ayu Kartika Dewi, Kadek; Hafidz, Jawade (UNISSULA Semarang, 2025)
The problem raised in this study originated from a case of aggravated theft recorded in the Denpasar District Court Decision Number 666/Pid.B/2025/PN Dps. This case involved a defendant named Ade Muhamad Wijaya, who was charged with violating the provisions of Article 363 paragraph (1) 5 of the Criminal Code (KUHP) regarding theft committed with aggravated elements. Research methods play a central role in legal scholarly work because they are the primary instrument for answering problem formulations systematically and purposefully. In legal research, a methodological approach must be able to connect legal norms and practices in the field, while also providing space for contextual and equitable legal interpretation. Therefore, the methods used in this research are designed to depict law not only as a normative text but also as a system of values that lives within society. This research uses a juridical-normative research method, namely legal research that emphasizes the study of written legal norms, such as statutory regulations, court decisions, and the doctrines of legal experts. Juridical-normative research focuses on law as a rule that should apply (das sollen), rather than as empirical social behavior (das sein). Application of Article 363 paragraph (1) 5 of the Criminal Code in Decision Number 666/Pid.B/2025/PN Dp: The Denpasar District Court, through Decision Number 666/Pid.B/2025/PN Dps, has correctly applied the provisions of Article 363 paragraph (1) 5 of the Criminal Code, because the defendant's actions fulfill the elements of aggravated theft. The aggravating element lies in the theft being committed under certain circumstances that have more serious consequences than ordinary theft.